2022
DOI: 10.1007/s12144-021-02656-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of novel instruments of brand communication and brand image in building consumers’ brand preference and intention to visit wineries

Abstract: This research aims to analyze brand communication and brand image as specific drivers of wine brand preference and their influence on wine consumers’ intention to visit associated wineries. Specifically, this paper enhances the understanding of the roles of advertising-promotion, sponsorship-public relations, corporate social responsibility, and social media in brand communication, as well as functional, emotional and reputation components in brand image development in the context of wine tourism industry. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 66 publications
0
25
0
2
Order By: Relevance
“…Lang et al (2022) adopted a more holistic approach and examined the impact of the promotion mix on the brand equity of low-involvement products, finding a significant impact of advertising and sponsorship. Similarly, Gómez-Rico et al (2022) discovered that brand communication measured in terms of advertising-promotion, sponsorship-public relations, corporate social responsibility and social media, affected positively brand image and brand preference in the winery tourism industry.…”
Section: Conceptual Framework and Research Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Lang et al (2022) adopted a more holistic approach and examined the impact of the promotion mix on the brand equity of low-involvement products, finding a significant impact of advertising and sponsorship. Similarly, Gómez-Rico et al (2022) discovered that brand communication measured in terms of advertising-promotion, sponsorship-public relations, corporate social responsibility and social media, affected positively brand image and brand preference in the winery tourism industry.…”
Section: Conceptual Framework and Research Modelmentioning
confidence: 98%
“…Lang et al , 2022), image (e.g. Gómez-Rico et al , 2022), perceived quality (e.g. Lang et al , 2022) and loyalty (e.g.…”
Section: Data Analysis and Findingsmentioning
confidence: 99%
“…PLS-SEM is indicated in research that wants to test or expand theoretical propositions, as used in these research studies (Lunkes et al, 2020;Hair et al, 2022;Rodrigues, Wander and Da Rosa, 2023). PLS is widely used in wine tourism studies (e.g., Gómez-Rico et al, 2023;Martínez-Falcó et al, 2023), and very suitable for the size of our sample of 123 responses.…”
Section: Measurement and Analysis Of Datamentioning
confidence: 99%
“…Though traditional research methodologies, such as bibliometric analysis (Martinho, 2021;Weatherbee et al, 2019) and systematic reviews (Campo et al, 2022;Carollo et al, 2022;Schäufele and Hamm, 2017), have long been employed to analyze and synthesize knowledge within wine business domains, an integrating these approaches offers a unique opportunity to gain comprehensive insights into wine consumers' behavior. It is found that most of the reviews pertain to particular theme, such as wine tourism experience (Gómez et al, 2019;Kotur, 2023), wine consumption (Wright et al, 2023), sustainability in wine industry (Nave et al, 2021), sustainable wine (Maesano et al, 2019), and willingness to pay (Schäufele and Hamm, 2017). Additionally, none of these reviews attempts to encompass the entirety of wine consumption.…”
Section: Introductionmentioning
confidence: 99%